Telaah Interdisipliner tentang Hakikat Kebenaran: Perspektif Filsafat, Sains, dan Agama Islam dalam Konteks Pendidikan Islam Integral - Al Kahfi, Musa; Rossidy, Imron (Khidmatussifa: Journal of Islamic Studies, 2025)
Truth, as a multidimensional concept, can be understood through various perspectives: philosophy, science, and Islam. Philosophy views truth through theories such as correspondence, coherence, and pragmatism, each offering a distinct epistemological framework for understanding reality. Science, with its scientific method, conceptualizes truth through empirical observation that can be verified. Meanwhile, in Islam, truth is regarded as divine revelation, absolute, and serves as a guiding principle for human life. Though differing in methodology, these three perspectives complement one another in forming a comprehensive understanding of the nature of truth. In the context of integrative Islamic education, there is a need to integrate religious knowledge and general knowledge into a comprehensive tauhid-based system. This study aims to explore the relevance of these three perspectives of truth in the development of integrative Islamic education. The method used is a qualitative approach with library research, gathering data from primary sources discussing the nature of truth, as well as secondary sources such as scholarly articles and previous research. The data are analyzed using content analysis to draw valid and objective conclusions. The findings show that the integration of philosophy, science, and Islam is highly relevant in creating a holistic education curriculum, producing a generation that is not only intellectually proficient but also balanced in moral and spiritual dimensions. Keywords: Sains, Religion, Islamic Education